Villagers’ attitudes and behaviors toward rural solid waste management under environmental authoritarianism in China - Li, Hui; Huang, Diejun; Li, Hua; Ma, Qiuzhuo; Li, Juan (Frontiers in Environmental Science, 2023)
In China, rapid urbanization and industrialization, combined with a rural-urban dual structure, have resulted in serious rural solid waste challenges. By issuing a list of regulations and guidelines and putting in huge amounts of special funds, the Chinese-style top-down linear and authoritarian waste governance has gained great achievements, seeing the national village-level coverage rate of the rural waste management system grown from zero to over 90% in less than 20 years. This paper provides qualitative insights into the factors that influence villagers’ responses (attitudes and behaviors) to the authoritarian environmental policy measures. With primary data from Meizhou County in Guangdong Province (the poorest county in China’s richest province), the study finds out that villagers’ attitudes are significantly affected by their satisfaction with the government’s rural solid waste management (RSWM) and their environmental concern, while villagers’ behaviors are significantly affected by their approval level to the local environment, the availability of solid waste collection facilities, and their environmental concern. Thus, villagers’ solid waste collection behaviors are influenced mainly by practical convenience and internal motivation. Government-relevant factors do not directly impact villagers’ solid waste collection behaviors, but significantly moderate villagers’ behaviors. Surprisingly, the variable of villagers’ education level is a significantly negative factor in affecting both RSWM attitudes and behaviors, which implies that future RSWM policy measures should take more democracy into consideration and value villagers’ participation.